2021
DOI: 10.1155/2021/5551662
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ and Preceptors’ Experiences with Using an Assessment Tool for Feedback and Reflection in Supervision of Clinical Skills: A Qualitative Pilot Study

Abstract: Background. There is a need to improve students’ learning in clinical practice. Undergraduate students need guidance when it comes to transferring knowledge from the classroom to clinical practice in community health services. Competence Development of Practical Procedures (COPPs), a simulation assessment tool, was used to explore students’ and preceptors’ experiences with feedback and reflection during the supervision of clinical skills in real practice. Method. This was a pilot study with a qualitative explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, with the increased need for educating competent nurses who can meet patients with complex health needs, several studies focusing on preceptorship in the context of primary care have been conducted (Frøiland et al, 2021;Gonella et al, 2019;Ong et al, 2021;Plathe et al, 2021). Although these studies convey the idea that nursing homes offer students learning opportunities, none described fundamental care as the content of the learning activities during students' first-year clinical placement.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the increased need for educating competent nurses who can meet patients with complex health needs, several studies focusing on preceptorship in the context of primary care have been conducted (Frøiland et al, 2021;Gonella et al, 2019;Ong et al, 2021;Plathe et al, 2021). Although these studies convey the idea that nursing homes offer students learning opportunities, none described fundamental care as the content of the learning activities during students' first-year clinical placement.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Several studies focusing on nurse preceptorship have been conducted in specialized units or acute care within a hospital context (Macey et al, 2021; Widiawati et al, 2021) or mental care setting (Vuckovic et al, 2019; Vuckovic & Landgren, 2021). However, with the increased need for educating competent nurses who can meet patients with complex health needs, several studies focusing on preceptorship in the context of primary care have been conducted (Frøiland et al, 2021; Gonella et al, 2019; Ong et al, 2021; Plathe et al, 2021). Although these studies convey the idea that nursing homes offer students learning opportunities, none described fundamental care as the content of the learning activities during students' first‐year clinical placement.…”
Section: Introductionmentioning
confidence: 99%
“…This work burden has a negative effect on their relationships with new nurses 7 ; as a result, new nurses may not receive adequate support from their preceptors, which may increase their turnover 8 . In fact, preceptor feedback in the clinical field provides new nurses with opportunities for self-reflection and helps them learn more effectively 12 . Although receiving appropriate feedback on their strengths and weaknesses may help new nurses better adapt to their clinical environments, 13 studies have found that new nurses do not often receive such feedback 14 .…”
mentioning
confidence: 99%
“…Furthermore, for preceptor nurses to perform their roles optimally, it is necessary for them to recognize new nurses as adult learners, provide regular evaluations and feedback, and increase their level of empathy and consideration 13,15,16 . Preceptor nurses may contribute to new nurses' positive learning experiences and growth by sharing their experiences with new nurses in addition to them giving formal direction and constructive feedback 12 …”
mentioning
confidence: 99%
See 1 more Smart Citation